Teacher's Efforts in Shaping the Character of Students Addicted to the TikTok Application in Elementary Schools - Haidir Haidir; Mardianto Mardianto; Dandi Irawan Sembiring; Muhammad Yusri; Ramadan Syah Putra (Jurnal Basicedu, 2023)
This study aims to see how the behavior of today's children towards the tik tok application. The formulation of the research problem is how to influence the use of the Tik-Tok application on the behavior of children in Binjai City. The purpose of this research is to find out how the use of the Tik-Tok application influences the behavior of children in Binjai City. The type of research used in this study is a type of qualitative research. The informants of this study were Maura El Mumtaz students who used the Tik-Tok application as many as 25 people aged 8-10 years. The results of this study can be concluded that the efforts made by the MIS teacher Maura El Mumtaz include: (1) Giving messages about adab and manners; (2) Provide consequences for students' bad behavior that violates the class agreement on polite behavior; (3) Teachers are also not allowed to play tick tock, this is because they are more likely to see people than them; (4) inviting parents to work together in overcoming student morals; and (5) Invite children to be positive.